Perlindungan Hukum Terhadap Data Pribadi Pada Penggunaan Platform Digital Berupa Akun Game Online - Panjaitan, Nadya Fransisca (Jurnal Ilmiah Wahana Pendidikan, 2024)
One of the electronic systems, Online Games, can only be accessed via electronic devices. Online gaming is now not just a game; it is a business platform for online game application providers. Emerging problems related to users' inability to protect their personal data and virtual property when using online gaming applications prompted this research. With the increasing use of internet technology, there are new challenges to keeping personal data safe, especially with improvements in the practices used to collect, use, and disseminate personal data. The protection of customers' personal data is very important for telecommunications service providers to establish clear legal relationships between businesses and their consumers. Currently, there are a number of laws governing the protection of personal data. Consisting of general laws (lex generalis) and special laws (lex specialis), Indonesian law regarding personal data protection has not been regulated in one law, so it does not meet general personal data protection principles. Protection of personal data of internet users and legal action against Facebook user data in Indonesia.